2020
DOI: 10.1038/s41598-020-70171-2
|View full text |Cite
|
Sign up to set email alerts
|

A Markov chain model of particle deposition in the lung

Abstract: These forces contribute to the particle's probability of escape from or deposition in a given airway. This probability in turn depends on numerous factors such as the length, diameter and orientation of the airway, as well as the flow rate due to breathing or mechanical ventilation. In principle, the probability of escape from a single pipe can be utilized to compute the total probability that a particle traverses the entire airway tree without capture. The goal of this study was to develop a Markov chain form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The MPPD model uses semi-empirical relationships in the upper airway and solves flow and deposition in the lower respiratory tract made of cylindrical airways. Other approaches include stochastic models accounting for the asymmetry of the airway tree ( Koblinger and Hofmann, 1990 ) and more recently a model incorporating a Markov chain formulation of particle motion ( Sonnenberg et al, 2020 ).…”
Section: The Fate Of Inhaled Aerosols In the Respiratory Systemmentioning
confidence: 99%
“…The MPPD model uses semi-empirical relationships in the upper airway and solves flow and deposition in the lower respiratory tract made of cylindrical airways. Other approaches include stochastic models accounting for the asymmetry of the airway tree ( Koblinger and Hofmann, 1990 ) and more recently a model incorporating a Markov chain formulation of particle motion ( Sonnenberg et al, 2020 ).…”
Section: The Fate Of Inhaled Aerosols In the Respiratory Systemmentioning
confidence: 99%
“…Based on picking up physical construction information and establishing a virtual model, it is necessary to fuse the information of time and space dimensions and establish a data analysis model for the safety assessment. Markov chain [31] is a tool for the immediate transfer process and an important branch of machine learning. In this mode, the structural state of the next period is only related to the state of this period, while each period before this period is irrelevant.…”
Section: Space-time Information Fusion In Construction Processmentioning
confidence: 99%
“…Particulate matter has comprehensively been recognized as one of the major threats to human health (Kan et al 2007;Zhang et al 2021). Particles emitted from contaminant sources such as vehicles and biomass-burning may be inhaled by both adults and children (Buonanno et al 2013;Díaz-Robles et al 2014;Deng et al 2018), and further deposition can be easily observed in human respiratory systems (Lin et al 1994;Oravisjärvi et al 2011;Sonnenberg et al 2020). Since nowadays people spend near 90% of their lifetime indoors (Klepeis et al 2001), the personal exposure level of particulate pollutants is directly determined by the quality of air within buildings.…”
Section: Introductionmentioning
confidence: 99%